Survival outcomes in a prospective randomized multicenter Phase III trial comparing patients undergoing anatomical segmentectomy versus standard lobectomy for non-small cell lung cancer up to 2 cm - Stamatis, Georgios; Leschber, Gunda; Schwarz, Birte; Brintrup, Diana Lütke; Flossdorf, Sarah; Passlick, Bernward; Hecker, Erich; Kugler, Christian; Eichhorn, Martin E.; Krbek, Thomas; Eggeling, Stephan; Hatz, Rudolf; et al. (Lung cancer: targets and therapy, 2022)
Objectives - The oncological equivalence of anatomical segmentectomy for early stage non-small cell lung cancer (NSCLC) is still controversial. Primary aim of this study was survival outcomes in combination with improved quality of life after segmentectomy compared with lobectomy in patients with pathological stage Ia NSCLC (up to 2 cm, 7th edition) - Materials and Methods - We conducted a prospective, randomized, multicenter phase III trial to confirm the non-inferiority of segmentectomy to lobectomy in regard to prognosis (trial No. DRKS00004897). Patients were randomized to undergo either segmentectomy or lobectomy and followed up for 5-years survival and tumor recurrence. The 5-year hazard ratio comparing lobectomy with segmentectomy was required to remain above 0.5. - Results - Between October 2013 and June 2016, 108 patients with verified or suspected NSCLC up to 2 cm diameter were enrolled; 54 were assigned to lobectomy and 54 (1 drop-out) to segmentectomy. In-hospital and 90 days mortality was 0% in both groups. Overall survival at 5 years was 86.52% in the lobectomy compared to 78.21% in the segmentectomy group (HR = 0.61, (95% CI 0.23-1.66), p-value of non-inferiority test, p-ni = 0.687). Disease free survival was 77.29% for the lobectomy and 77.96% for the segmentectomy patients (HR = 1.50, (95% CI 0.60-3.76), p-ni = 0.019). At a median follow-up of 5 years, no differences were noted in either the locoregional or distant recurrent disease in both groups (9.4% vs 7.4%, p-ni = 0.506). - Conclusion - Overall survival, locoregional and distant recurrences was not significantly difference for patients undergoing either segmentectomy or lobectomy for stage Ia NSCLC. The targeted non-inferiority of segmentectomy to lobectomy could not be proven for primary endpoint overall survival, but was significant for the secondary endpoint of disease free survival.